On some shared and distinguishing features of Nercha and Khamnigan Ewenki dialects - Bayarma Khabtagaeva (Language Science Press, 2022)
The present paper is a brief addition to the author’s recent monograph (Khabtagaeva 2017) which deals with Mongolic elements in Ewenki dialects (Barguzin, Nercha, Baunt and North-Baikal) spoken in the territory of Buryatia, Russia. Today Nercha Ewenki is no longer spoken. During the initial years of Soviet rule (ca. 1918–1932) some Nercha speakers crossed the border into Manchuria, China, and today their descendants are speakers of Manchurian Khamnigan Ewenki. The aim of this paper is to find out similarities and differences between the extinct Nercha Ewenki dialect and Manchurian Khamnigan Ewenki.